Responses of vegetation to different land-use histories involving grazing and fire in the North-east Patagonian Monte, Argentina - Peter, Guadalupe (2013)
In arid and semiarid lands around the world, vegetation is distributed in patches within a bare soil matrix. Vegetation in the North-east Patagonian Monte, Argentina is a shrubland steppe, and patches are dominated by shrubs, with grasses, forbs and cryptogams under their canopy. It was hypothesised that grazing increases patchiness; and fires and wind erosion homogenise the distribution of vegetation. It was predicted that there would be: (1) greater cover, specific frequency and richness of shrubs in grazed sites; (2) greater cover, specific frequency and richness of herbs and preferred grasses in ungrazed sites; and (3) a random pattern of distribution in burnt areas. Aerial cover of all perennial species was measured at six sites with different land-use histories: heavily grazed, medium grazed, ungrazed, long exclosure from grazing followed by grazing, burnt and then ungrazed, and burnt and then grazed. Species were grouped into five functional types: shrubs, subshrubs, preferred grasses, non-preferred grasses and forbs. The results showed significant differences in the cover of preferred and non-preferred grasses, forbs and total cover with previous grazing but there was no evidence of shrub encroachment. Species frequency and richness decreased especially with increased grazing intensity. The pattern of spatial distribution changed from aggregated in grazed sites to random in ungrazed and burnt sites for all plant functional types. At the population level, the cover of the grass, Poa ligularis, was greatest on ungrazed sites whereas the cover of the shrub, Chuquiraga erinacea, was greatest on burnt sites. It is concluded that, after applying a heterogeneous patchwork of disturbance, such as grazing, or with fire, followed by periods of rest, the plant diversity is increased.